1993
DOI: 10.1128/aac.37.4.662
|View full text |Cite
|
Sign up to set email alerts
|

Ciprofloxacin resistance in clinical isolates of Salmonella typhimurium obtained from two patients

Abstract: Two patients (patients A and B) infected with Salmonella typhimurium failed ciprofloxacin therapy, and the posttherapy isolates had reduced susceptibilities to quinolones; 6 of 11 isolates from patient B were also cross-resistant to chemically unrelated agents. No transferable resistance, chloramphenicol-acetylating enzymes, or 13-lactamases were detected. For 13 of 14 isolates, the concentrations of ciprofloxacin that inhibited DNA synthesis by 50%o were similar to the MICs, suggesting a mutation in gyrA. Ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
73
0
3

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(81 citation statements)
references
References 23 publications
5
73
0
3
Order By: Relevance
“…A few studies have reported on alterations of outer membrane protein expression or of lipopolysaccharide in quinolone-resistant Salmonella [18,20,56,57]. However, it does not appear clearly from these studies whether such alterations contributed significantly to decreased outer membrane permeability and consecutive quinolone resistance.…”
Section: Decreased Outer Membrane Permeabilitymentioning
confidence: 69%
See 1 more Smart Citation
“…A few studies have reported on alterations of outer membrane protein expression or of lipopolysaccharide in quinolone-resistant Salmonella [18,20,56,57]. However, it does not appear clearly from these studies whether such alterations contributed significantly to decreased outer membrane permeability and consecutive quinolone resistance.…”
Section: Decreased Outer Membrane Permeabilitymentioning
confidence: 69%
“…The role in Salmonella quinolone resistance of mutations in the target genes, in particular in gyrA and gyrB, has been confirmed by complementation studies using wild-type genes on plasmids [16,20,23,54,56,57]. It nevertheless remains to be determined what the exact impact of these mutations is on quinolone resistance, as has been done for E. coli constructed isogenic mutants where mutations in gyrA and parC were experimentally introduced in the absence of quinolone selection [4].…”
Section: Target Gene Mutationsmentioning
confidence: 97%
“…Antibiotic resistance, particularly to ciprofloxacin [minimum inhibitory concentration (MIC) ≥0.5 μg/mL], occurred and increased in the isolates along the time course of infection (Table 1; susceptibility data for other antibiotics have been previously published and are shown in Table S2) (14,15,18). Previously, the MDR was attributed to increased expression of the acrB transcript (18).…”
Section: Resultsmentioning
confidence: 99%
“…S1) (14,15). The isolates were obtained from a 52-y-old male patient admitted for repair of a leaking abdominal aortic aneurysm graft.…”
mentioning
confidence: 99%
“…In contrast to the findings in Enterobacter aerogenes and E. coli (8), ramA-mediated MDR in 5408-cip was not associated with downregulation of porins. Few studies have investigated OmpF expression in fluoroquinolone-resistant Salmonella, and its contribution to resistance is unclear (14,29,35). Only one study to date has documented alterations in the LPS profile in fluoroquinolone-resistant Salmonella, and the authors suggested that the increase in the proportion of long O-chain LPSs observed could result in a lower level of antibiotic accessibility to the porins (14).…”
Section: Discussionmentioning
confidence: 99%